Isolation, characterization and evaluation of mosquitocidal activity of Lysinibacillus strains obtained from Culex pipiens larvae - Tranchida, María Cecilia (2011)
Three strains—C107, C207, and C307—of spore-forming Gram-positive motile rod-shaped bacteria were isolated from dead larvae of Culex pipiens in La Plata city, Argentina. The three bacterial strains have different phenotypic and molecular characteristics. A comparative analysis of their 16S rRNA gene sequences and phylogenetic analysis demonstrated that isolates C107 and C207 were related to reference strains of Lysinibacillus sphaericus, while C307 was related to Bacillus licheniformis. The cytomorphology, biochemical characterization, and phylogenetic relatedness corroborated these respective group assignments. The isolated bacterial strain exhibited the same PCR amplified pattern for the binA, binB, and mtx genes as did the reference strains used. These bacterial strains presented different pathogenic actions among the following mosquito species tested: Culex pipiens, Aedes aegypti, Culex dolosus, Culex apicinus, Ochlerotatus albifasciatus, and Anopheles albitarsis. Only isolates C107 and C207 exhibited mosquitocidal activity. Culex pipiens was the species most susceptible to C107 (LC₅₀, 4 × 10⁴ spores/ml), while O. albifasciatus was most susceptible to C207 (LC₅₀, 3.4 × 10⁶ spores/ml).